2013
DOI: 10.1038/npp.2013.232
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Tyrosine/Phenylalanine Depletion Effects on Behavioral and Brain Signatures of Human Motivational Processing

Abstract: Dopamine (DA) neurotransmission is critical for motivational processing. We assessed whether disruption of DA synthesis in healthy controls using an amino-acid beverage devoid of catecholamine precursors (tyrosine-phenylalanine depletion (TPD)) would blunt recruitment of the nucleus accumbens (NAcc) by rewards. Sixteen controls ingested each of a tyr/phe-depleting beverage (DEP) or a tyr/ phe-balanced (BAL) control beverage in two laboratory visits. Five hours after consumption of each drink, subjects underwen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
15
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 39 publications
6
15
0
Order By: Relevance
“…Indeed, Eisenberger et al (2010) demonstrated that endotoxin administration led to the reduced activation of ventral striatum to reward-predicting cues during a monetary incentive delay task, which was associated with increases in self-reported depressed mood as measured by the Profile of Mood States depression subscale. Similar blunting of neural responses to reward anticipation has been observed following dietary depletion of precursors for DA synthesis (Bjork et al, 2014). Moreover, typhoid vaccination was found to cause a shift in reward vs punishment sensitivity in a probabilistic instrumental learning task combined with fMRI (Harrison et al, 2015b).…”
Section: Neuroimaging Of the Da System And Corticostriatal Reward Cirsupporting
confidence: 58%
“…Indeed, Eisenberger et al (2010) demonstrated that endotoxin administration led to the reduced activation of ventral striatum to reward-predicting cues during a monetary incentive delay task, which was associated with increases in self-reported depressed mood as measured by the Profile of Mood States depression subscale. Similar blunting of neural responses to reward anticipation has been observed following dietary depletion of precursors for DA synthesis (Bjork et al, 2014). Moreover, typhoid vaccination was found to cause a shift in reward vs punishment sensitivity in a probabilistic instrumental learning task combined with fMRI (Harrison et al, 2015b).…”
Section: Neuroimaging Of the Da System And Corticostriatal Reward Cirsupporting
confidence: 58%
“…43 Yet, a larger study failed to detect independent influence of comorbid cocaine dependence on gray matter volume deficits in alcohol-dependent men. 41 Herein, although the alcohol-cocaine and alcohol-opiate groups had smaller frontal volumes than the drug-dependence-free alcohol-dependent participants, deficits in precentral, supplementary motor, and medial volumes endured when the analysis was limited to drugdependence-free alcohol-dependent participants.…”
Section: Alcohol and Drug Dependence Comorbiditymentioning
confidence: 80%
“…122 Dietary depletion of DA precursors, which reduces DA synthesis 123 , attenuates participants' sensitivity to rewards during decision-making 124 and also increases punishment learning relative to reward learning 125 , with some reporting corresponding reductions in reward-elicited BOLD responses in the striatum. 126 Research using DA receptor antagonists to block transmission has yielded less consistent results, possibly owing to doses used and the actions of these compounds on other monoamine systems as well as inhibitory autoreceptors. 122 L-DOPA (which increases DA synthesis), amphetamine and methylphenidate (which block DA reuptake) and D2/3 receptor agonists generally increase a variety of the processes depicted in Fig 1, including: speed 127 and vigour 128 of responses (action); effortful 61 and risky 129 choices (cost-benefit decision making); reward learning; 130 and associated reward-related striatal BOLD responses (reviewed in ref 109).…”
Section: Neuromodulatorsmentioning
confidence: 99%